Effect of clinical use of nickel-titanium springs - Magno, Amanda Fahning; Monini, André da Costa; Capela, Marisa Veiga [UNESP]; Martins, Lidia Parsekian [UNESP]; Martins, Renato Parsekian [UNESP] (Elsevier B.V., 2015)
Introduction: Our objectives were to determine whether there are changes on the load deflection rate (L/DP) and the average force (FP) of the superelastic pseudoplateau, and whether permanent deformation is changed in nickel-titanium closed-coil springs (CCSs) after 6 months of clinical use. Methods: Twenty-two nickel-titanium CCSs (Sentalloy 100 g; Dentsply GAC, York, Pa) were subjected to tensile mechanical testing at 37 degrees C on activations varying from 3.2 to 16.0 mm before and after 6 months of clinical use. A regression line was fitted over the most horizontal area of the unloading part of the stress-strain graph of every CCS, and its slope was used as L/DP. The FP was determined by the midpoint of the longest segment of the curve that could be fit within the regression line with a R-2 of at least 0.999, and permanent deformation was determined graphically by obtaining the strain value when the measured stress reached zero. The data were analyzed by 3 analyses of variance at 2 levels, with 5% of significance. Results: Time and activation significantly influenced the variables tested (P < 0.001). Time increased the L/DP and permanent deformation but decreased the FP. Activation decreased L/DP, FP, and permanent deformation. Significant interactions between time and activation were detected for FP (P = 0.013) and deformation (P < 0.001). Conclusions: After 6 months of active clinical use, the analyzed springs had a significant but small increase in their L/DP; FP dropped up to 88%, and the CCSs deformed up to 1.26 mm.